Molecular and functional differences in voltage-activated sodium currents between GABA projection neurons and dopamine neurons in the substantia nigra - Ding, Shengyuan (American Physiological Society, 2011)
GABA projection neurons (GABA neurons) in the substantia nigra pars reticulata (SNr) and dopamine projection neurons (DA neurons) in substantia nigra pars compacta (SNc) have strikingly different firing properties. SNc DA neurons fire low-frequency, long-duration spikes, whereas SNr GABA neurons fire high-frequency, short-duration spikes. Since voltage-activated sodium (Na(V)) channels are critical to spike generation, the different firing properties raise the possibility that, compared with DA neurons, Na(V) channels in SNr GABA neurons have higher density, faster kinetics, and less cumulative inactivation. Our quantitative RT-PCR analysis on immunohistochemically identified nigral neurons indicated that mRNAs for pore-forming Na(V)1.1 and Na(V)1.6 subunits and regulatory Na(V)β1 and Na(v)β4 subunits are more abundant in SNr GABA neurons than SNc DA neurons. These α-subunits and β-subunits are key subunits for forming Na(V) channels conducting the transient Na(V) current (I(NaT)), persistent Na current (I(NaP)), and resurgent Na current (I(NaR)). Nucleated patch-clamp recordings showed that I(NaT) had a higher density, a steeper voltage-dependent activation, and a faster deactivation in SNr GABA neurons than in SNc DA neurons. I(NaT) also recovered more quickly from inactivation and had less cumulative inactivation in SNr GABA neurons than in SNc DA neurons. Furthermore, compared with nigral DA neurons, SNr GABA neurons had a larger I(NaR) and I(NaP). Blockade of I(NaP) induced a larger hyperpolarization in SNr GABA neurons than in SNc DA neurons. Taken together, these results indicate that Na(V) channels expressed in fast-spiking SNr GABA neurons and slow-spiking SNc DA neurons are tailored to support their different spiking capabilities.